Prevalence of Pediatric Asthma Risk in Santo Domingo, Dominican Republic - Wendy W. Sun (Ubiquity Press, 2017)
Background: Early detection and treatment of pediatric asthma could reduce morbidity and lessen burden on society. Currently there is no known research on the prevalence of pediatric asthma in the Dominican Republic (DR) and no known asthma risk assessment tool for one-time encounters in a fast-paced clinic. Objectives: To pilot a streamlined version of previously validated screening tools to estimate the prevalence of pediatric asthma risk in Santo Domingo Norte, DR. Methods: A combined asthma questionnaire and clinical assessment tool was developed and administered to patients aged 2-12 years. Findings: We found that 25.7% of the 74 study participants were categorized as probable asthma, 21.6% were at high risk for asthma, 14.9% elevated risk, and 37.8% not at risk. Conclusion: If the prevalence of 25.7% is representative of the DR as a whole, the DR would have one of the highest national rates in Latin America. The study assessment tool was convenient to use, but tool validation is needed.